1989
DOI: 10.1103/physreva.40.5040
|View full text |Cite
|
Sign up to set email alerts
|

Classical periodic motion of atomic-electron wave packets

Abstract: An experiment is described in which a coherent superposition of the Rydberg states of atomic potassium is excited by a short optical pulse. The coherent superposition forms a wave packet localized in the radial coordinate. The radial motion of the wave packet is periodic with the period of the classical Kepler orbit. The time evolution is probed by a second short pulse. The resulting photoionization signal, as a function of the delay between pulses, shows the classical periodicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 9 publications
1
53
0
3
Order By: Relevance
“…Alber and co-workers proposed a scheme for generating electron wave packets with laser pulses [9]. Ten Wolde et al [10,11] and Yeazell et al [12,13] independently demonstrated radially as well as angularly localized electron wave packets, observed via the revival of the electron density on a (sub-)picosecond time scale.The experiment involves a tunable extreme ultraviolet (XUV) nanosecond laser source, based on third harmonic generation in a pulsed gas jet; this system and the method of separating the XUV from the fundamental UV, obtained from a frequency-doubled pulsed dye laser, as well as other technicalities were described before [14]. The XUV source, operated at 92.3 nm, is tuned on resonance with P͑1͒, R͑0͒, and R͑1͒ B 2 X(17,0) Lyman band transitions of H 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alber and co-workers proposed a scheme for generating electron wave packets with laser pulses [9]. Ten Wolde et al [10,11] and Yeazell et al [12,13] independently demonstrated radially as well as angularly localized electron wave packets, observed via the revival of the electron density on a (sub-)picosecond time scale.The experiment involves a tunable extreme ultraviolet (XUV) nanosecond laser source, based on third harmonic generation in a pulsed gas jet; this system and the method of separating the XUV from the fundamental UV, obtained from a frequency-doubled pulsed dye laser, as well as other technicalities were described before [14]. The XUV source, operated at 92.3 nm, is tuned on resonance with P͑1͒, R͑0͒, and R͑1͒ B 2 X(17,0) Lyman band transitions of H 2 .…”
mentioning
confidence: 99%
“…Alber and co-workers proposed a scheme for generating electron wave packets with laser pulses [9]. Ten Wolde et al [10,11] and Yeazell et al [12,13] independently demonstrated radially as well as angularly localized electron wave packets, observed via the revival of the electron density on a (sub-)picosecond time scale.…”
mentioning
confidence: 99%
“…(5)- (8), it is easy to verify that T n n (0) = 1 for n = n and 0 for n = n. We shall present all results of this work by making use of (5) rather than (2). In close analogy with the result for the single kicked atoms [10], the autocorrelation function for the twice kicked atoms can be written as…”
Section: Wave Packet and Autocorrelation Functionmentioning
confidence: 94%
“…The Rydberg wave packets in atoms were first created by photoexcitation using ultrashort pulses [1,2]. But since the pioneering experiment of Jones et al [3], unipolar electric field pulses of tetrahertz spectrum, often called half-cycle pulses (HCPs), have been found to provide a very convenient tool to produce such packets.…”
Section: Introductionmentioning
confidence: 99%
“…While the question of achieving the classical limit of quantum dynamics of simple systems via appropriately constructed coherent states [11,12,13,14] has been a longstanding one, interesting experiments have been carried out recently to demonstrate such a classical limit in quantum systems [15]. More recently the classical limit of the commensurate anisotropic oscillator has been investigated experimentally [16] in a laser resonator by exploiting the analogy between the Schrödinger equation for the two-dimensional harmonic oscillator and the paraxial wave equation for the spherical resonators [17,18].…”
Section: Introductionmentioning
confidence: 99%